A new species of cryptic cyanobacteria isolated from the epidermis of a bottlenose dolphin and as a bioaerosol. Issue 6 (2nd November 2021) - Brown, Amber O.; Romanis, Caitlin S.; Dvořák, Petr; Foss, Amanda J.; Gibson, Quincy A.; Villanueva, Chelsea D.; Durden, Wendy N.; Garvey, Alyssa D.; Jenkins, Phillip; Hašler, Petr; Johansen, Jeffrey R.; Neilan, Brett A.; et al.
ABSTRACT: Two cyanobacterial strains, one collected from an epidermal mat present on a dead bottlenose dolphin and the other as a bioaerosol 457 m (1500 ft) above the river, were recently analysed from the St. Johns River, Jacksonville, Florida, USA. Both samples had major phenotypic plasticity which confused morphological identification. Amplicon sequencing of the 16S rRNA gene from the isolates revealed that both samples were closely aligned (branch bootstrap support = 100%) with the recently erected genus Komarekiella . Whole genome sequencing and phylogenetic construction also supported the isolation of a new species of cyanobacteria branching from the Nostoc clade. A total evidence approach of molecular, genetic, and ecological examination of these strains supported the erection of a new species, Komarekiella delphini-convector . A prior study determined that the dolphin with the epidermal mat had low levels of microcystins/nodularins (MCs/NODs) in the hepatic tissue. To investigate whether these toxins originated from the epidermal mat, immunoassay (ELISA) and 2-methyl-3-methoxy-4-phenylbutyric acid (MMPB) techniques were conducted on the original mat and subsequent culture samples. The results from both analyses were not conclusive. Genome mining was conducted and revealed diverse biosynthetic capabilities of this species but could not support toxin-producing potential. Further analytical work is required to determine the pathogenic capacity of this epizoic species.